2016
DOI: 10.3892/mmr.2016.5808
|View full text |Cite
|
Sign up to set email alerts
|

Protocadherin γ A3 is expressed in follicular lymphoma irrespective of BCL2 status and is associated with tumor cell growth

Abstract: Protocadherin genes (PCDHs) have been suggested to act as tumor suppressor genes in various tumor types. Previous studies have demonstrated the upregulation of certain PCDH-γ subfamily genes in nodal and duodenal follicular lymphoma (FL) using gene expression analyses. However, the mechanisms and associated molecular function of PCDH-γ subfamily gene upregulation in FL remain to be elucidated. The present study examined the expression of PCDHGA3, an upregulated PCDH-γ gene subfamily member, in B-cell lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…DNA methylation levels at the 5′ regions of clustered PCDHA genes inversely correlate with gene expression levels, and 5-azacytidine treatment induces expression of silent PCDHA genes (Kawaguchi et al 2008). Hypermethylation is also associated with reduced expression of PCDHB and PCDHG genes (Dallosso et al 2009), and reduced or deregulated protocadherin expression is associated with various neurological, psychiatric, and cardiovascular disorders, and tumor growth (Dallosso et al 2009;Ortega et al 2016;Zhang et al 2016;El Hajj et al 2017). Interestingly, hypermethylation at the promoter regions of the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation levels at the 5′ regions of clustered PCDHA genes inversely correlate with gene expression levels, and 5-azacytidine treatment induces expression of silent PCDHA genes (Kawaguchi et al 2008). Hypermethylation is also associated with reduced expression of PCDHB and PCDHG genes (Dallosso et al 2009), and reduced or deregulated protocadherin expression is associated with various neurological, psychiatric, and cardiovascular disorders, and tumor growth (Dallosso et al 2009;Ortega et al 2016;Zhang et al 2016;El Hajj et al 2017). Interestingly, hypermethylation at the promoter regions of the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PCDHGA, PCDHGB, PCDHGC) may contribute to cell migration and invasion. Previous studies have confirmed that PCDH genes were involved in tumorigenesis and metastasis of gastric cancer, follicular lymphoma and non-small cell lung cancer (Mukai et al, 2017;Zhang et al, 2016;Zhou et al, 2017), although other studies have found that PCDH genes were implicated in tumor suppression (Chen et al, 2017;Weng et al, 2018). However, the role of PCDH genes in MLL-R ALL is currently unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Homophilic cell adhesion, mediated by the up-regulation of protocadherin ( PCDH ) γ subfamily of genes (e.g., PCDHGA , PCDHGB , PCDHGC ) may contribute to cell migration and invasion. Previous studies have confirmed that PCDH genes were involved in tumorigenesis and metastasis of gastric cancer, follicular lymphoma and non-small cell lung cancer (Mukai et al, 2017; Zhang et al, 2016; Zhou et al, 2017), although other studies have found that PCDH genes were implicated in tumor suppression (Chen et al, 2017; Weng et al, 2018). However, the role of PCDH genes in MLL -R ALL is currently unclear.…”
Section: Discussionmentioning
confidence: 98%